(untitled) (Medical Forum Monthly, 2024)
Objective: To compare operative1 laparoscopy vs laparotomy in the management of haemodynamically stable patients with ectopic pregnancy. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Sheikh Zaid Hospital, Rahim Yar Khan from October 2017 to April 2018. Materials and Methods: Total 72 married females of reproductive age (15-49 years) presenting in emergency/OPD of Obstetrics & Gynecology with suspected diagnosis of ectopic pregnancy till 8 weeks of gestation confirmed by transvaginal ultrasound, haemodynamically stable patients as defined in operational definitions having ß-hCG< 6000 IU/L were included in the study. In study group A, laparoscopy was performed and in group B laparotomy was performed. Operative duration, postoperative hospital stay and wound infection was compared between the both groups. Results: A total of 72 patients were selected for this study. Mean age of the patients was 27.56±4.23 and 25.56±4.15 years in group-A and B, respectively. In group-A, mean gestational age was 6.0±1.2 weeks and in group group-B 5.7±1.1 weeks. In laparoscopy group (A), no wound infection was noted but in laparotomy group (B), there were 4 (11.1%) patients found with wound infection. Statistically significantly difference between wound infection of both groups was noted with p value 0.040. In group A mean duration of operation was 79.89 ± 2.90 and in group B was 95.94 ± 2.55 minuets. Mean post operative hospital stay was 1.06 ± 0.23 days in group A while 3.17 ± 1.44 days in group B. Conclusion: In conclusion, laparoscopic treatment of ectopic pregnancy yielded superior benefits over laparotomy in terms of less operative time and less postoperative hospital stay. Additionally, laparoscopy has a great role in diagnosis of clinically suspicious cases. Therefore, laparoscopy should be opted whenever possible.